Ketidakterkaitan Antara Impor, Utang Luar Negeri Dan Pertumbuhan Ekonomi Di Indonesia Pada Tahun 2018-2022 - Wisda Zulaeha Suwardi; Nurhidayati Islamiyah (STIM-LPI Makassar, 2023)
This study aims to describe the value of imports in Indonesia, the description of Indonesia's foreign debt, the description of economic growth in Indonesia, and the effect of imports and foreign debt on economic growth either simultaneously or partially. The data analysis method used is descriptive statistical analysis to find out the description of each variable, product moment correlation analysis, and will be continued in multiple linear regression analysis if there is a significant relationship to determine the relationship between variables either simultaneously or partially. The data sources used in this study are: secondary data in this study were obtained from Indonesia's macroeconomic data for 2018-2022. Data on import values ​​were obtained from the publication of data from the Ministry of Trade, data on foreign debt were obtained from publications by Bank Indonesia, and economic growth was obtained from publications from the Central Bureau of Statistics. The results of the study show that the picture of imports in Indonesia in the 2018-2022 period is in the moderate category. The description of foreign debt in the 2018-2022 period is in the moderate category. The description of Indonesia's economic growth in the 2018-2022 period is in the high category. The results of data processing show that there is a positive relationship between imports and economic growth, but it is not significant. Foreign debt has a negative relationship with economic growth but not significant.